2012
DOI: 10.5762/kais.2012.13.3.1212
|View full text |Cite
|
Sign up to set email alerts
|

Effect of The Trunk Muscle Stabilization Training on Balance for Chronic Stroke Patients

Abstract: This study was to investigate the balancing and clinical abilities trunk muscle stabilization exercise and trunk muscle resistive exercise of stroke patients having surface changes in balance of body. The subjects of this study were 30 stroke patients(15 males and 15 females) that three times a week for 12 weeks at the same time point and with the same amount of exercise. They were separated into two groups and did reinforcing exercise on trunk muscle stabilization exercise and trunk muscle resistive exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Also, TSE was found more effective upon between-group comparison. Lee et al (2012) randomized 30 hemiplegia patients to the TSE and trunk resistance exercise group and showed that BBS significantly improved after the intervention in both groups, and TSE was considered to be an appropriate exercise method for improving BA. Shim et al (2014) randomized 15 subjects with hemiplegia due to stroke to an NDT and CG based on TSE and showed significant improvement in BBS in both groups, but the comparison between-groups showed significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…Also, TSE was found more effective upon between-group comparison. Lee et al (2012) randomized 30 hemiplegia patients to the TSE and trunk resistance exercise group and showed that BBS significantly improved after the intervention in both groups, and TSE was considered to be an appropriate exercise method for improving BA. Shim et al (2014) randomized 15 subjects with hemiplegia due to stroke to an NDT and CG based on TSE and showed significant improvement in BBS in both groups, but the comparison between-groups showed significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, training of t’ai chi chuan for 12 weeks failed to increase bone density but it decreased rates of bone loss. Also, Han 14 ) performed resistance exercise program targeting 11 women after menopause for 6 weeks and measured bone density of lumbar and femur. There was not a meaningful difference statistically in this result but bone density of lumbar increased.…”
Section: Discussionmentioning
confidence: 99%
“…Japan) and Quantitative Computed Tomography before and after experiment and BMC (Bone Mineral Contents) was tested using mean value of bone density of lumbar 1st and 4th. Trunk stability exercise used by Lee et al 14 ) was used as spinal and pelvic stabilization exercise. It is composed of step1 (awareness stage), step 2 (associative stage), and step 3 (exercise task stage) according to basis of research of O’Sullivan.…”
Section: Methodsmentioning
confidence: 99%
“…The trunk stability exercise described by Lee et al13, 14 ) was used as spinal and pelvic stabilization exercise. It is composed of step 1 (awareness stage), step 2 (associative stage), and step 3 (exercise task stage) based on the research of Ok stage)15 ) .…”
Section: Methodsmentioning
confidence: 99%